Optimizing the Better Nights, Better Days for Children with Neurodevelopmental Disorders program for large scale implementation - Ilie, Alzena; Orr, Matt; Weiss, Shelly; Smith, Isabel M.; Reid, Graham J.; Hanlon-Dearman, Ana; Brown, Cary; Constantin, Evelyn; Godbout, Roger; Shea, Sarah; Ipsiroglu, Osman S.; Corkum, Penny V. (Frontiers in Sleep, 2023)
Objective: Pediatric insomnia is one of the most commonly reported disorders, especially in children with neurodevelopmental disorders. Better Nights, Better Days for Children with Neurodevelopmental Disorders (BNBD-NDD) is a transdiagnostic, self-guided, eHealth behavioural sleep intervention developed for parents of children with NDDs ages 4-12 years with insomnia. After usability testing, a randomized controlled trial (RCT) was conducted to evaluate the effectiveness of the BNBD-NDD program. By interviewing RCT participants after their outcome measures were collected, we sought to determine the barriers and facilitators that affect the reach, effectiveness, adoption, implementation, and maintenance of the BNBD-NDD intervention, as well as to assess whether barriers and facilitators differ across levels of engagement with the program and NDD groups. Method: Stratified sampling was used to select 20 parents who had been randomized to the treatment condition of the RCT. These parents participated in virtual semi-structured qualitative interviews about their experiences with the BNBD-NDD program. Rapid analysis was used, in which one researcher facilitated the interview, and another simultaneously coded the interview using the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) framework. Results: Overall, more facilitators than barriers were identified for Reach, Effectiveness, Implementation, and Maintenance, whereas for Adoption more barriers emerged. Participants who were engaged reported more facilitators about the BNBD-NDD program design and behaviour change, while unengaged participants mentioned needing more support to help facilitate their use of the program. Lastly, parents of children with ASD reported more facilitators and more barriers than did parents of children with ADHD. Conclusion: With this feedback from participants, we can optimize BNBD-NDD for large-scale implementation, by modifying the program to better support parents, helping them implement the strategies effectively at home, and increasing the accessibility of this evidence-based treatment.